USE OF INNOVATIVE TECHNOLOGIES BY INSURANCE MARKET ENTITIES. TELEMATICS IN CAR INSURANCE - Ignatovich, Liliya (Three seas economic journal, 2020)
The purpose of the article is to substantiate the need for the use of innovative technologies by participants in the insurance market, namely, telematics in car insurance. The current state of the financial services market requires insurers to raise standards of work through the introduction of innovative products. It is determined that increasing the competitiveness of an insurance company should focus on providing the best personal services and meet the requirements of modernity and modern social trends, and therefore, make full use of the Internet: marketing and innovation. In view of this, the key task of the insurer’s innovation activity is the maximum approximation of insurance services to the existing needs of the insured in insurance protection. It is possible to reach stable demand for this or that insurance service under the conditions of application of the world innovative insurance programs providing balance of qualitative and quantitative parameters of the insurance contract only. The relevance of the topic is that the Ukrainian insurance companies are forced to look for new opportunities to meet the needs of their customers in order to maintain competitive advantages and work effectively in the conditions of innovative development of insurance activity in the world. A promising area of further research is to assess the readiness of insurance market participants to use innovative insurance services. Methodology. The essence of telematics in car insurance is investigated. The state of the CASCO insurance market in Ukraine is analyzed. The main advantages of telematics use by the subjects of the insurance market of Ukraine are determined. Practical implications. It is proved that the introduction of innovative technologies opens new opportunities for the growth of additional premiums, improving the quality of service and minimizing insurance risks. Theoretical provisions on the need for ways to improve the innovative activities of the insurer have been further developed.